2019
DOI: 10.1016/j.ebiom.2019.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Early increase of specialized pro-resolving lipid mediators in patients with ST-elevation myocardial infarction

Abstract: Background Termination of acute inflammation is an active process orchestrated by lipid mediators (LM) derived from polyunsaturated fatty acids, referred to as specialized pro-resolving mediators (SPM). These mediators also provide novel therapeutic opportunities for treating inflammatory disease. However, the regulation of these molecules following acute myocardial infarction (MI) remains of interest. Methods In this prospective observational study we aimed to profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…19,36 Before troponin markers, leucocyte-directed SPMs are immune responsive polyunsaturated fatty acids-derived biomolecules generated within a narrow time window after the cardiac injury that initiate resolution of inflammation. 20,36 Deficiency of SPMs associated with monocyte/macrophage depletion or in obesogenic ageing leads to non-resolving inflammation. 20,37 Ethyl EPA lowered the risk of MI events, stroke, and overall CV death by 25% in patients with hypertriglyceridaemia in the REDUCE-IT trial and by 19% in the JELIS trial, suggesting preventive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,36 Before troponin markers, leucocyte-directed SPMs are immune responsive polyunsaturated fatty acids-derived biomolecules generated within a narrow time window after the cardiac injury that initiate resolution of inflammation. 20,36 Deficiency of SPMs associated with monocyte/macrophage depletion or in obesogenic ageing leads to non-resolving inflammation. 20,37 Ethyl EPA lowered the risk of MI events, stroke, and overall CV death by 25% in patients with hypertriglyceridaemia in the REDUCE-IT trial and by 19% in the JELIS trial, suggesting preventive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Time-dependent cardiac repair in pathogen and risk-free rodents clearly suggests that the timing of the acute inflammatory phase coincides with the beginning of the resolving phase, to the same extent as MI patients biosynthesize resolution molecules within 2.5 h as the onset of initial inflammation post-MI. 20,33,36 Thus, beginning of acute inflammation-resolution programmes the termination of inflammatory response after cardiac injury of acute inflammation programmes the beginning of inflammatory resolution after cardiac injury. 43 A previous report indicates that SPMs levels in atheroma define the stable and unstable milieu, providing the rationale for precise and personalized therapy for atherosclerotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma concentrations of SAMPs, here SPM profiles, have also been measured using liquid chromatographytandem mass spectrometry (LC-MS) technology [49,50]. Of note, in a recently published evaluation of SPM profiles using an optimized LC-MS method for the detection of SPMs in biological samples, Kutzner et al [51] concluded, "SPMs were generally not detectable/quantifiable in plasma and serum of healthy individuals, while good recovery rates were found in spiked samples.…”
Section: Plasma Concentration Of Hmgb1 S100 Proteins Circulating Dnmentioning
confidence: 99%